2020
DOI: 10.1002/mnfr.202000593
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Hippo Pathway by Food Allergen Exacerbates Intestinal Epithelia Instability and Facilitates Hypersensitivity

Abstract: Scope Hippo signaling is a crucial pathway in innate immune responses, but the relationship between food allergy and Hippo pathway is unknown. The aim of this work is to investigate the regulation of food allergy by Hippo pathway and reveal the molecular mechanisms. Methods and results Two food allergens tropomyosin and ovalbumin are used to challenge a mouse model and CMT93 intestinal epithelia cell model. The allergic responses and the activation of Hippo pathway are tested in these models. In the mouse mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Therefore, a growing body of research is focusing on the development of advanced in vitro mucosal immune models to allow effective safety and allergenicity risk assessment of novel food proteins and to provide tools for further mechanistic studies without the use of animal models ( 10 ). Recent attempts have aimed to develop sensitizing allergenicity models up till the T cell response ( 11 , 12 ), however the use of murine cells may lack translational value to study food allergy from a human perspective. In a similar approach we recently showed the contribution of epithelial cells in driving the first steps of allergic sensitization ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a growing body of research is focusing on the development of advanced in vitro mucosal immune models to allow effective safety and allergenicity risk assessment of novel food proteins and to provide tools for further mechanistic studies without the use of animal models ( 10 ). Recent attempts have aimed to develop sensitizing allergenicity models up till the T cell response ( 11 , 12 ), however the use of murine cells may lack translational value to study food allergy from a human perspective. In a similar approach we recently showed the contribution of epithelial cells in driving the first steps of allergic sensitization ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has demonstrated the involvement of the Hippo pathway in food allergy using a mouse model ( 12 ). To further validate this finding and check the capability of the 3D intestinal cell model in food allergy research, the activation of the Hippo pathway was determined in this model.…”
Section: Resultsmentioning
confidence: 99%
“…The total protein from cells was extracted by Tissue Total Protein Lysis Buffer (Sangon Biotech, China), and the Western blot analysis was conducted with indicated antibodies as previously reported ( 12 ). In brief, 40 μg of total protein extract was denatured in loading buffer containing β-mercaptoethanol and SDS at 95°C and then loaded to each lane of a polyacrylamide gel (5% stacking gel and 12% separating gel).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations